NANOGOETHITE IS THE DOMINANT REACTIVE OXYHYDROXIDE PHASE IN LAKE AND MARINE SEDIMENTS - van der Zee C.; Roberts D.R.; Rancourt D.G.; Slomp C.P. (My University, 2003)
Iron oxides affect many elemental cycles in aquatic sediments via numerous redox reactions and their large sorption capacities for phosphate and trace elements. The reactive ferric oxides and oxyhydroxides are usually quantified by operationally defined selective chemical extractions that are not mineral specific. We have used cryogenic 57Fe Mö ssbauer spectroscopy to show that the reactive iron oxyhydroxide phase in a large variety of lacustrine and marine environments is nanophase goethite (a-FeOOH), rather than the assumed surface-complex stabilized, two-line ferrihydrite and accompanying mixture of clay and oxyhydroxide Fe-bearing phases. This result implies that the kinetic and stability parameters of the type of nanogoethite that we observe to be present in sediments should be first determined and then used in models of early diagenesis. The identity and characteristics of the reactive phase will also set constraints on the mechanisms of its authigenesis.
Keywords: iron oxides; goethite; Messbauer spectroscopy; early diagenesis; sediments